Distributed enterprise modelling guided by business rules - Di Paolo, Nahuel (2002)
Enterprise architectures create a technical platform to meet current and future business needs. In this sense, architectural components ensure IT capabilities are modelled in every business process. Current approaches to enterprise architecting tend to focus on reducing the effort required to design business processes by using the resources provided by the Web to support new inter-organisational processes. This often leads to the development of services where some generic features or rules are particularly similar across different processes. We describe and illustrate the use of business rules to share components across many different views. Having a business rule front end lets a component offer different access rights and visibility to different clients. We present an approach that might be used in the process of enterprise architecting in conjunction with a service-oriented perspective.